2022
DOI: 10.1136/jitc-2022-005111
|View full text |Cite
|
Sign up to set email alerts
|

COLAR: open-label clinical study of IL-6 blockade with tocilizumab for the treatment of immune checkpoint inhibitor-induced colitis and arthritis

Abstract: BackgroundImmune-related adverse events due to immune checkpoint inhibitors (ICIs) are not always effectively treated using glucocorticoids and it may negatively affect the antitumor efficacy of ICIs. Interventional studies of alternatives to glucocorticoids are lacking. We examined whether interleukin-6 blockade by tocilizumab reduced ICI-induced colitis and arthritis.Patients and methodsPatients with solid cancer experiencing Common Terminology Criteria for Adverse Events (CTCAE v5.0) grade >1 ICI-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…The biologic tocilizumab, an IL-6 receptor antagonist, a key drug in rheumatoid arthritis [109], has shown clinical efficacy in 79% of the cohort in a retrospective study including 34 patients with a grade 3-4 irAE (pneumonitis, 35%; serum sickness, 35%; colitis, 3%) [110]. In addition, tocilizumab has been investigated in patients with ICI-induced colitis (COLAR trial; 19 patients with colitis/arthritis) in a preliminary study published after our final search of April 21, 2021 [111]. The authors concluded that tocilizumab showed promising clinical efficacy in the treatment of ICI-induced arthritis and/or colitis, as 80% of patients with colitis had ≥ 1 grade improvement in symptoms.…”
Section: Tablementioning
confidence: 99%
“…The biologic tocilizumab, an IL-6 receptor antagonist, a key drug in rheumatoid arthritis [109], has shown clinical efficacy in 79% of the cohort in a retrospective study including 34 patients with a grade 3-4 irAE (pneumonitis, 35%; serum sickness, 35%; colitis, 3%) [110]. In addition, tocilizumab has been investigated in patients with ICI-induced colitis (COLAR trial; 19 patients with colitis/arthritis) in a preliminary study published after our final search of April 21, 2021 [111]. The authors concluded that tocilizumab showed promising clinical efficacy in the treatment of ICI-induced arthritis and/or colitis, as 80% of patients with colitis had ≥ 1 grade improvement in symptoms.…”
Section: Tablementioning
confidence: 99%
“…Although the precise mechanism remains unclear, ICIs block negative signals on activated T cells, leading to increased autoreactive T cells and inflammatory cytokines such as tumor necrosis factor-α (TNF-α), IL-6, and IL-17 [ 62 , 63 , 64 ]. This provides the rationale for targeted inhibition of these cytokines to treat rheumatic irAEs [ 65 , 66 ]. ICIs can also induce epitope spreading, diversifying the epitope specificity of T cells [ 62 ].…”
Section: Rheumatic Iraesmentioning
confidence: 99%
“…As mentioned above, the use of abatacept should be avoided because of the risk of antagonizing the anti-tumor effects of ICIs [ 77 ]. There is no evidence in the literature to suggest a preference for one biologic DMARD over another: infliximab, adalimumab, etanercept, tocilizumab, and sarilumab have controlled symptoms [ 56 , 66 , 92 ].…”
Section: Rheumatic Iraesmentioning
confidence: 99%
“…Very limited clinical reports on the use of IL-6 blockade for irAEs do not show impaired ICI efficacy 111 114 . Stroud et al reported on 87 nivolumab treated patients, of whom 34 patients received tocilizumab (anti-IL-6R) for severe irAEs 111 .…”
Section: Interleukin-6 Blockadementioning
confidence: 99%
“…Similarly, Dimitriou et al report a median PFS of 6 months in 22 advanced melanoma patients receiving tocilizumab 113 , which is difficult to compare given the variety of ICI regimens patients received. The COLAR study (NCT03601611) demonstrated that 6 out of 20 patients treated with tocilizumab alone for ICI colitis or arthritis had progressive disease 114 . Although a 14 day period without any immunosuppression was required prior to tocilizumab initiation, 9 of the 20 patients had received systemic corticosteroids, including 3 who had also received infliximab for any irAEs prior to tocilizumab administration 114 .…”
Section: Interleukin-6 Blockadementioning
confidence: 99%